MENSTRUAL HYGIENE KNOWLEDGE AND PRACTICES AMONG SCHOOL ADOLESCENT GIRLS IN RURAL COMMUNITY, LAHORE, PAKISTAN - AKBAR , S; KHALIL , A; HAMEED , R; KHALEEL , F; TASLEEM , F; ZAFAR , M; FIRDOUS , U (Biological and Clinical Sciences Research Journal, 2024)
Menstrual hygiene management (MHM) is critical for the health and well-being of adolescent girls, yet cultural taboos, inadequate education, and limited access to sanitary facilities pose significant challenges, particularly in rural Pakistan. Objective: To assess the knowledge, practices, and hygiene habits of adolescent schoolgirls regarding menstrual hygiene in a rural community in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 108 adolescent schoolgirls aged 10–18 years. Data were collected using a structured questionnaire addressing knowledge, practices, and hygiene habits related to menstruation. Descriptive statistics were analyzed using SPSS version 26. Results: Most participants (84.3%) were aware of menstruation, but only 31.48% received information before menarche. Mothers were the primary source of information (98.15%), while only 64.81% used sanitary pads. Privacy issues in washing absorbents were reported by 68.49%, and only 38.15% used soap for cleaning. School absenteeism due to menstruation was reported by 72.22% of participants, largely due to pain and lack of toilet facilities. Conclusion: Significant gaps in menstrual hygiene knowledge and practices exist among adolescent girls in rural Pakistan. Interventions focusing on school-based education, community awareness, and improved access to hygiene products and facilities are urgently needed to address these gaps and promote better health and educational outcomes.